Shikonin Prevents Early Phase Inflammation Associated with Azoxymethane/Dextran Sulfate Sodium-Induced Colon Cancer and Induces Apoptosis in Human Colon Cancer Cells - Andújar, Isabel; Martí-Rodrigo, Alberto; Giner, Rosa María; Ríos, José Luis; Recio, María Carmen (Planta Medica, 2018)
Shikonin is the main active principle in the root of Lithospermum erythrorhizon, widely used in traditional Chinese medicine for its anti-inflammatory and wound healing properties. Recent research highlights shikoninʼs antitumor properties and capacity to prevent acute ulcerative colitis. The aim of the present study was to evaluate the ability of shikonin to prevent, in vivo, the early phases of colorectal cancer development, with special focus on its cytotoxic mechanism in vitro. We employed the azoxymethane/dextran sulfate sodium model of colitis in Balb/C mice. Body weight and drinking were monitored throughout the experiment, and length of colon and lesions of the colon were recorded on termination of the experiment in all of the experimental groups. Colons underwent histological evaluation and biochemical analyses [myeloperoxidase activity assay, measurement of interleukin-6, evaluation of proinflammatory enzymes (cyclooxygenase-2 and inducible nitric oxide synthase), and nuclear factor-κB activation by Western blot]. Caco-2 cells were used to evaluate, in vitro, the effect of shikonin on proliferation, cytotoxicity, cell cycle, and apoptosis. Our results reveal that shikonin significantly protected the intestinal tissue of our animals by preventing the shortening of the colorectum and ulcer formation in a dose-dependent manner. Shikonin attenuated the expression of cyclooxygenase-2 and inducible nitric oxide synthase, and myeloperoxidase activity, and inhibited the production of interleukin-6 and activation of nuclear factor-κB. It induced Bcl-2 and inhibited caspase 3. In conclusion, shikonin acts as a chemopreventive agent in the azoxymethane/dextran sulfate sodium model through inhibition of the proinflammatory milieu generated during the disease, an important risk factor in cancer development.
Keywords: Lithospermum erythrorhizon; Boraginaceae; inflammatory bowel disease; shikonin; ulcerative colitis; in vivo